2017
DOI: 10.1007/s11136-017-1756-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in a broader perspective: Does ASCOT reflect the capability approach?

Abstract: PurposeEconomic evaluation of services and interventions in care services tends to focus on quality of life(QoL) based on health-related measures such as EQ5D, with a major focus on health and functioning. The Capability Approach (CA) provides an alternative framework for measuring QoL and challenges some of the conventional issues in the current practice of measurement of QoL. The Adult Social Care Outcomes Toolkit (ASCOT) aims to measure social care-related QoL in a broad sense. This article investigates whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The AQoL-8D is an Australian-based PBM [15,56], which was included as it has a strong focus on psychosocial domains. The ICECAP-O [19] and ASCOT [20] were included given that their focus on social care and capabilities is relevant to elderly populations [57,58]. DEMQOL-U [26,59] and AD-5D [28,29] were considered because of their focus on dementia-specific issues.…”
Section: Methodsmentioning
confidence: 99%
“…The AQoL-8D is an Australian-based PBM [15,56], which was included as it has a strong focus on psychosocial domains. The ICECAP-O [19] and ASCOT [20] were included given that their focus on social care and capabilities is relevant to elderly populations [57,58]. DEMQOL-U [26,59] and AD-5D [28,29] were considered because of their focus on dementia-specific issues.…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative measure, it might be interesting for future studies to use a cancer-specific, or even palliative cancer-specific utility instrument alongside the EQ-5D to investigate the cost-utility of supportive care interventions among incurably ill cancer patients [ 33 ]. In addition, it might be worthwhile to measure HRQOL from a broader perspective than just the ‘health perspective’; for example by using the Adult Social Care Outcomes Toolkit (ASCOT) [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the CA can help to understand what really matters to older adults who receive care. A previous study showed that the ASCOT can be regarded as an operationalization of the CA (Van Loon, Van Leeuwen, Ostelo, Bosmans, & Widdershoven, 2018). The answer options in the additional domains of the EQLT are also in line with the CA, as they are operationalized as functionings.…”
Section: Discussionmentioning
confidence: 99%